2004
DOI: 10.1002/14651858.cd001209.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for preventing recurrent urinary tract infection in non-pregnant women

Abstract: BackgroundUrinary tract infection (UTI) is a common health care problem. Recurrent UTI (RUTI) in healthy non-pregnant women is defined as three or more episodes of UTI during a twelve month period. Long-term antibiotics have been proposed as a prevention strategy for RUTI. ObjectivesTo determine the e icacy (during and a er) and safety of prophylactic antibiotics used to prevent uncomplicated RUTI in adult nonpregnant women. Search methodsWe searched MEDLINE (from 1966), EMBASE (from 1980), Cochrane Central Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
228
1
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(256 citation statements)
references
References 54 publications
5
228
1
14
Order By: Relevance
“…Women with RUTIs were more likely to experience symptoms after intercourse, have a previous history of pyelonephritis, and experience rapid resolution of symptoms postantibiotic therapy than those women with irritative voiding symptoms. 5,6 Moreover, women with RUTIs were more unlikely to report nocturia and have symptoms between episodes of UTI than women without infection. The presence of irritative voiding symptoms between perceived episodes of UTI suggests a non-infectious cause as seen in interstitial cystitis, urethral syndrome or detrusor muscle overactivity.…”
Section: Management Of Recurrent Urinary Tract Infections (Rutis)mentioning
confidence: 99%
See 3 more Smart Citations
“…Women with RUTIs were more likely to experience symptoms after intercourse, have a previous history of pyelonephritis, and experience rapid resolution of symptoms postantibiotic therapy than those women with irritative voiding symptoms. 5,6 Moreover, women with RUTIs were more unlikely to report nocturia and have symptoms between episodes of UTI than women without infection. The presence of irritative voiding symptoms between perceived episodes of UTI suggests a non-infectious cause as seen in interstitial cystitis, urethral syndrome or detrusor muscle overactivity.…”
Section: Management Of Recurrent Urinary Tract Infections (Rutis)mentioning
confidence: 99%
“…34 A variety of antimicrobials are used for the prevention and management of RUTIs. 6,15,24,29,33,[38][39][40][41] A Cochrane review has shown that antibiotics in comparison to a placebo are more effective in preventing recurrences in pre-and postmenopausal women with RUTIs. 6 The criteria for the selection of the most effective antibiotic depend on a patient's pattern of resistance, adverse effects, interaction with drugs and cost.…”
Section: A N T I M I C R O B I a L T H E R A P Ymentioning
confidence: 99%
See 2 more Smart Citations
“…Meta-analiza koju je sprovela Cochrane Database, a koja je obuhvatila 10 studija sa 430 žena, pokazala je da je posle primenjene kontinuirane terapije relativni rizik za ponovnu infekciju po bolesniku godišnje 0,15. Neželjena dejstva su bila vaginalna i oralna kandidijaza, gastrointestinalni simptomi i ospa [25]. Kontinuirana profilaksa antimikrobnim lekovima sprovodi se svakodnevno ili tri puta nedeljno tokom 6-12 meseci.…”
Section: Mere Profilakse Rekurentnih Infekcija Mokraćnih Putevaunclassified